Model Pengelolaan Irigasi Memperhatikan Kearifan Lokal - Supadi, Supadi (MEDIA KOMUNIKASI TEKNIK SIPIL, 2008)
Irrigation Management which across through provinces, regencies, and located in one regency of the Irrigation Area (DI) had different level of difficulty,  in spite of technical problems, it is also influenced by  factors of society behavioral. Then, irrigation management based on the technical and behavioral of the society to its local wisdom that sourced from the local cultural innovation was interested to be analyzed. The local wisdom potency which was based on its own autonomy and independence will be beneficial optimally and directed positively in many kinds of forms and efforts to overcome problems related to effectiveness and efficiency of irrigation system management. The location of the research was determined randomly from 12 provinces which consist of 37 regencies in Java and outside of Java. The aims of this research were identifying irrigation regulation, the service water irrigation, the physical condition of irrigation network, implementation of Governmental Regulation, analysis between manifest variable correlation with construct variable and  construct variable with others construct  variable, interpretation of test hypothesis for each of latent variable, the influence analysis to the used of  water in  irrigation, and formulation of policy in irrigation  management. Thus, the development of model to manage irrigation based on local wisdom using variable of technical and social aspect were interested to be analyzed. Keywords: Irrigation Management, Irrigation Area, local wisdom, scenarioPermalink: http://ejournal.undip.ac.id/index.php/mkts/article/view/2276[How to cite: Supadi (2008), Model Pengelolaan Irigasi Memperhatikan Kearifan Lokal, Jurnal Media Komunikasi Teknik Sipil, Tahun 16, Nomor 3, pp. 269-278]